Odpowiedź :
Odpowiedź:
a) f(x) = 2[tex]x^{2}[/tex] g(x) = - 2[tex]x^{2}[/tex]
b) f(x) = 2[tex]x^{2}[/tex]-3x+4 g(x) = - 2[tex]x^{2}[/tex] + 3x - 4
c) f(x) = 3[tex]x^{2}[/tex] - [tex]\sqrt{3-x}[/tex] +4 g(x) = - 3[tex]x^{2}[/tex] + [tex]\sqrt{3-x}[/tex] - 4
d) f(x) = 2[tex]x^{2}[/tex] + [tex]\sqrt{4+x}[/tex] + 5 g(x)= - 2[tex]x^{2}[/tex] - [tex]\sqrt{4+x}[/tex] - 5
Szczegółowe wyjaśnienie:
Symetria względem osi OX powoduje zmianę znaku przed przekształcaną funkcją
[tex]S_{OX}[/tex]
f(x) ---------------------------> g(x) = - f(x)